2020
DOI: 10.1093/asj/sjaa207
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Self-Reported Health Complaints and Health-Related Quality of Life in Women With Breast Implants

Abstract: Background Millions of women have silicone breast implants (SBI). Some report a pattern of systemic complaints, also referred to as ASIA syndrome. However, the association between these complaints and breast implants remains uncertain. Objectives This study aimed to evaluate the prevalence of complaints in women with breast implants and healthy controls, and to compare their health-related quality of life (HRQoL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…Worrying statements in journalism, such as in ‘The implant files', contribute to unrest among women with breast implants [ [29] , [30] , [31] ]. In very few cases, the use of breast implants can lead to breast implant illness [ [32] , [33] , [34] ]. Removal of the implants improves health complaints in half of the patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Worrying statements in journalism, such as in ‘The implant files', contribute to unrest among women with breast implants [ [29] , [30] , [31] ]. In very few cases, the use of breast implants can lead to breast implant illness [ [32] , [33] , [34] ]. Removal of the implants improves health complaints in half of the patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, a comparative study on the prevalence of health complaints in SBI patients showed that health complaints were only higher in a group of selfreported women who made their complaints public in an online platform compared to controls. 10 The adjusted prevalence of self-reported health complaints were not found to be significantly higher in SBI patients who did not made their complaints public in comparison to control patients without SBI. 10 Women who reported their complaints online (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…10 The adjusted prevalence of self-reported health complaints were not found to be significantly higher in SBI patients who did not made their complaints public in comparison to control patients without SBI. 10 Women who reported their complaints online (e.g. social media and internet worrying patients) are expected to have the most severe complaints and thus do not constitute a representative control group for the entire SBI population due to selection bias.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, observational studies including appropriate comparison groups do not show a difference in prevalence of non-specific complaints between women with and without SBIs. 6 , 7 Meticulous studies in large, unselected groups of women need to either confirm or refute the existence of the controversial syndrome that breast implant illness is. In the Netherlands, several hospitals are currently collaborating to provide more insight into these important questions.…”
mentioning
confidence: 99%